2014
DOI: 10.1016/j.bbrc.2014.01.165
|View full text |Cite
|
Sign up to set email alerts
|

EPO-independent functional EPO receptor in breast cancer enhances estrogen receptor activity and promotes cell proliferation

Abstract: The main function of Erythropoietin (EPO) and its receptor (EPOR) is the stimulation of erythropoiesis. Recombinant human EPO (rhEPO) is therefore used to treat anemia in cancer patients. However, clinical trials have indicated that rhEPO treatment might promote tumor progression and has a negative effect on patient survival. In addition, EPOR expression has been detected in several cancer forms. Using a newly produced anti-EPOR antibody that reliably detects the full-length isoform of the EPOR we show that br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…Furthermore, EPOR receptor was shown to enhance ER activity and promote cell proliferation (58). Several correlations between EPOR, ER, and other steroid receptors expression have been described (54, 55, 59, 60).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EPOR receptor was shown to enhance ER activity and promote cell proliferation (58). Several correlations between EPOR, ER, and other steroid receptors expression have been described (54, 55, 59, 60).…”
Section: Introductionmentioning
confidence: 99%
“…More controversially, rhEPO has been reported to negatively affect outcomes among patients receiving chemotherapy for certain cancers including breast, head/neck, and additional malignancies 15, 36-39 . The extent to which tumor cells express EPORs at meaningful densities is also controversial, but EPOR expression levels overall are quite low-level 40-42 , and with recent notable exceptions 40, 41, 43 most EPOR antibodies are not so sensitive or specific 40, 42 . In studies using an A82 EPOR antibody, EPOR expression in a human cancer cell line panel was nominal 44 .…”
Section: ] Epo and Present Clinical Uses Of Rhepomentioning
confidence: 99%
“…In xenograft experiments for several human cancer cell lines no significant effects of rhEPO on tumor growth were observed 45 , and in a study of primary tumor cells from 186 patients, rhEPO did not significantly activate AKT or MAPK signaling 46 . Nonetheless, in recent studies using an antiserum to a hEPO C-terminal epitope, EPOR expression has been reported among breast cancer cell lines, and associated with estrogen receptor-alpha activation 43 . Via RNAi approaches, the EPOR furthermore has been indicated to modulate tumor cell growth, survival and/or migration in melanoma 47 , renal carcinoma 48 and breast cancer cell lines 43 .…”
Section: ] Epo and Present Clinical Uses Of Rhepomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have additionally shown that the conversion rate in obese people is higher than that in lean people. Estrogen level is positively correlated with body weight (Du et al, 2014;Reinbothe et al, 2014). After menopause, estrogen level gradually declines while body fat content increases.…”
Section: Introductionmentioning
confidence: 99%